Integrated arrangement of advanced power electronics through hybrid smart grid system - Nelly Safitri; A. M. Shiddiq Yunus; Fauzi Fauzi; Naziruddin Naziruddin (Universitas Ahmad Dahlan, 2020)
As an enabler component for renewable energy integration, power electronics (PE) technology in smart grid system is one of the most important issues of development the electrification, decentralization and information-technology/operation-technology (IT/OT) digitization within the electrical energy transmission and distribution systems. The arrangement of PE may different along the feeder either for grid-connected photovoltaic (PV), wind turbine, fuel cells, wave energy system and battery storage unit, respectively.This is due to the electric voltage that might need to be converted from alternating current (AC) to direct current (DC) and vice versa. For that reason, this paper proposed a concept of advanced PE as an integrated arrangement of several AC/DC/AC-and DC/AC- converters in such ways that support thepreviously mentioned grid-connected hybrid renewable energy sources and distributed generators (DGs) along the distribution feeder. Additionally, for the system that supported by battery storage unit, then this hybrid smart grid concept might become the answer for future utility needs.